Language Teacher Wellbeing in the Workplace - Sonja Babic; Sarah Mercer, Univ.-Prf. Dr.; Astrid Mairitsch, Mag.; Johanna Gruber, Mag.; Kirsten Hempkin (Theory and Practice of Second Language Acquisition, 2022)
Teachers who experience high wellbeing in their workplace teach more effectively, have better relationships with learners, and high attainment among their learners (Mason, 2017). To understand what contributes to language teacher wellbeing, we examined the three pillars of positive psychology (Seligman, 2011) and drew in particular on work in Positive Organizational Scholarship (Cameron & Spreitzer, 2012) to explore institutional and personal factors which teachers perceived as influential for their wellbeing. The paper reports on insights from 15 language teachers in 13 different countries. This sampling technique ensured a diverse set of perspectives on this topic. Data were gathered through in-depth, semi-structured interviews which were analyzed using Thematic Analysis (Braun & Clarke, 2006). The analysis revealed five main themes the teachers perceived as relevant for their wellbeing including workplace culture, social relationships, sense of meaning and purpose, language teacher status, and physical wellbeing. The findings highlight that wellbeing is not just a personal and subjective phenomenon, but it is also collectively and socially determined. The study concludes with a reflection on implications for practice, policy makers, and school leaders as well as a consideration of issues of individuality to address in future research.